Adult listening behaviour, music preferences and emotions in the mobile context. Does mobile context affect elicited emotions?. Issue 1 (1st January 2019) - Fabio, Rosa Angela; Iannizzotto, Giancarlo; Nucita, Andrea; Caprì, Tindara
Abstract: After the introduction of mobile computing devices, the way people listen to music has changed considerably. Although there is a broad scientific consensus on the fact that people show music preferences and make music choices based on their feelings and emotions, the sources of such preferences and choices are still debated. The main aim of this study is to understand whether listening in ecological (mobile) contexts differs from listening in non-mobile contexts in terms of the elicited emotive response. A total of 328 participants listen to 100 classical music tracks, available through an ad-hoc mobile application for mobile devices. The participants were asked to report their self-evaluation of each of the tracks, according to the Pleasure-Arousal-Dominance model and filled out a questionnaire about their listening behaviour. Our findings show that the same factors that affect music listening in non-mobile contexts also affect it in a mobile context.